Low‐dose gemcitabine depletes regulatory T cells and improves survival in the orthotopic Panc02 model of pancreatic cancer. Issue 1 (10th January 2013) - Shevchenko, Ivan; Karakhanova, Svetlana; Soltek, Sabine; Link, Julia; Bayry, Jagadeesh; Werner, Jens; Umansky, Viktor; Bazhin, Alexandr V.
<x xml:space="preserve">Abstract</x> Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive human neoplasms with extremely poor prognosis and a low survival rate. Immunosuppressive cell populations, e.g. regulatory T cells (Treg), appear to be important in PDAC, contributing to patient's poor prognosis. Therefore, we investigated the PDAC microenvironment with a focus on conventional and regulatory T cells in view of their potential therapeutic importance. We found that tumors from the murine Panc02 orthotopic model of PDAC were infiltrated with high numbers of Treg. Remarkably, these cells exhibited the effector/memory phenotype, suggesting their enhanced suppressive activity and higher proliferation capacity. Although we observed a steady increase in transforming growth factor‐β (TGF‐β) levels in the tumors, treatment with a specific inhibitor of TGF‐β receptor I kinase failed to abrogate Treg accumulation. A CCR4 antagonist did not affect Treg percentage in the tumor either. However, intense Treg cell division in the tumor microenvironment was demonstrated, suggesting local proliferation as a major mechanism of Treg accumulation in PDAC. Notably, this accumulation was reduced by low‐dose gemcitabine administration, resulting in a modestly increased survival of PDAC mice. Our results provide an insight into mechanisms of immunosuppression in PDAC, suggesting an important role for proliferative expansion of effector/memory Treg. Low‐dose gemcitabine therapy selectively depletes Treg, providing a basis for new modalities of PDAC therapy.